Triskeles and Symmetries of Mean Global Sea-Level Pressure - Fernando Lopes; Vincent Courtillot; Jean-Louis Le Mouël (Atmosphere, 2022)
The evolution of mean sea-level atmospheric pressure since 1850 is analyzed using iterative singular spectrum analysis. Maps of the main components (the trends) reveal striking symmetries of order 3 and 4. The Northern Hemisphere (NH) displays a set of three positive features, forming an almost perfect equilateral triangle. The Southern Hemisphere (SH) displays a set of three positive features arranged as an isosceles triangle, with a possible fourth (weaker) feature. This geometry can be modeled as the Taylor–Couette flow of mode 3 (NH) or 4 (SH). The remarkable regularity and three-order symmetry of the NH triskeles occurs despite the lack of cylindrical symmetry of the northern continents. The stronger intensity and larger size of features in the SH is linked to the presence of the annular Antarctic Oscillation (AAO), which monitors the periodic reinforcement and weakening of the circumpolar vortex; it is a stationary mode. These components represent 70% of the variance in total pressure since 1850 and are stable in both time and space. In the remaining 30% of the variance, we have extracted quasi-periodical components with periods larger than 1 year (2% of the variance) and a harmonic sequence of the 1-year period (20% of the variance).